A Contrastive Analysis of Indonesian and English Declarative Sentences in News Article “6 Fakta Baru Kecelakaan Maut Cibubur Hingga Sopir-Kernet Truk Tersangka” on Detiknews Website - Soni, Roza Rapita; Manik, Labora; Sinaga, Rika; Samosir, Dona (International Journal Corner of Educational Research, 2023)
This research aims at contrasting two languages, including Indonesian as the source language (SL) and English as the target language (TL). This research data was taken from the news article “6 Fakta Baru Kecelakaan Maut Cibubur Hingga Sopir-Kernet Truk Tersangka” on detikNews website. The researchers used the qualitative method with textual analysis from books, journals and news as the data collection technique in this research. Based on the research result, the researchers found 29 declarative sentences from the news article. According to the text source, there are five similar patterns in Indonesian and English, including SP, SC, SPO, SPC and SPOC. And there are distinct patterns in Indonesian and English, setting them apart. Indonesian exhibits the SPOO and SCPC patterns, which are not found in English. Conversely, English showcases the SPSPC, SPOPC, and SPOCPC patterns not found in Indonesian. Additionally, these patterns are accompanied by varying phrases in each language.